Prakesh C Tiwari on Women's adaptive innovations - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Women's adaptive innovations in land and water management under climate change in Himalaya: An illustration of reducing gender gap in subsistence agricultural economy in marginalized environment Presentation by Prakesh C Tiwari from Kumaon University at the Closing the gender gap in farming under climate change event held 19 March 2015 in Paris. Read more about the event: https://ccafs.cgiar.org/events/closing-gender-gap-farming-under-climate-change-new-knowledge-renewed-action